2d(9d-4)=0

Simple and best practice solution for 2d(9d-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2d(9d-4)=0 equation:


Simplifying
2d(9d + -4) = 0

Reorder the terms:
2d(-4 + 9d) = 0
(-4 * 2d + 9d * 2d) = 0
(-8d + 18d2) = 0

Solving
-8d + 18d2 = 0

Solving for variable 'd'.

Factor out the Greatest Common Factor (GCF), '2d'.
2d(-4 + 9d) = 0

Ignore the factor 2.

Subproblem 1

Set the factor 'd' equal to zero and attempt to solve: Simplifying d = 0 Solving d = 0 Move all terms containing d to the left, all other terms to the right. Simplifying d = 0

Subproblem 2

Set the factor '(-4 + 9d)' equal to zero and attempt to solve: Simplifying -4 + 9d = 0 Solving -4 + 9d = 0 Move all terms containing d to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 9d = 0 + 4 Combine like terms: -4 + 4 = 0 0 + 9d = 0 + 4 9d = 0 + 4 Combine like terms: 0 + 4 = 4 9d = 4 Divide each side by '9'. d = 0.4444444444 Simplifying d = 0.4444444444

Solution

d = {0, 0.4444444444}

See similar equations:

| 7(6-2a)=(a+4) | | x^2+18x-49=0 | | 22y+128=6y | | 6+s=21 | | -2(a+3)=5(4-3a) | | 6(1+4v)-(11-v)=42 | | 9-4+x=2 | | 6-21=s | | N+15=45 | | X^2+32x-66=0 | | 4(k-3)=3(k-4) | | 4=-3-2 | | f(x)=4x(1+lnx) | | 21+s=6 | | (x+3)2+(y-4)2=36 | | 2.3x^2+2x+1=0 | | 4=x-30 | | Xsquare=64 | | K^2-10k-96=0 | | 0=480x-2x^2 | | 5=20x^2 | | 6+8+x=40 | | 2.18-g=9.5 | | 4x+(x+15)=180 | | 3(2c+1)=6 | | 16n-14-23n+26+9n=42 | | 3+5(-3)=y | | 23x-2y=29 | | 4x(x-15)=180 | | 1440=h+5x | | 12n-4(n-1)=2(n-2)-4 | | 3(2n-5)=2n-3 |

Equations solver categories